SHUKRALA (SPERMATOGENIC) POTENTIALITY OF MADHYAMA PANCHAMOOLA- A REVIEW (International Journal of Ayurveda and Pharma Research, 2021)
Propagation of human race get affected by both male and female factors. Male infertility contributes 50% of total infertility. Ksheenashukra (Oligospermia) is one of the commonest conditions for male infertility caused by Vata pitta dosha. Ayurvedic approach to rectify pathology of Ksheenashukra is through Vrushya (Aphrodisiac), Shukrajanaka, (Spermatogenic) Shukravardhaka (enhancing Semen and Sperm) Shukrapravataka (improve the ejaculatory process) and Shukrala etc pharmacological activities. The drug which enhances Shukra (Semen and Sperm) is named as Shukrala (Spermatogenic) activity. Madhyama panchamoola a group of drugs comprising of Bala (Sida cordifolia) Punarnava (Boerhavia diffusa), Eranda (Ricinus communis), Mudgaparni (Teramnus labialis) and Mashaparni (Vigna trilobata). Review of literature reveals that each of these drugs has Balya (Strength promoter), Vrushya, Rasayana (Rejuvenation), Jeevaniya (Life promoting) and Shukrajanana (Spermatogenic) properties. Madhyama panchamoola as a group not had been evaluated for its potentiality as Shukrala but each of them individually proven for antioxidant, spermatogenic, antidiabetic and hepatoprotective activities. Phytoconstituents present in this viz., Ecdysterone, Boeravinone, Rotenoids, Octacosanol, Vitexin, Quercetin and Bergenin have been confirmed for spermatogenic activity. Reactive oxygen species identified as cause for male infertility. Hence antioxidant is used as a source of treatment. Components of Madhyama panchamoola in addition to antioxidant activity have other required pharmacological activities in the management of Ksheenashukra. This review upholds the compatibility ingredients of Madhyama pancha moola to be potential Shukrala combination.